PENGARUH PENGGUNAAN MODEL AKTIVE LEARNING DENGAN STRATEGI CLARIFICATION PAUSES TERHADAP HASIL BELAJAR SEJARAH SISWA KELAS X SMA N 1 TEUNOM SEMESTER GANJIL TAHUN AJARAN, 2017-2018 - Kafrawi .; Anwar Yoesoef; Nurasiah . (Universitas Syiah Kuala, 2018)
The achievement or failure of educational goals planned by a teacher cannot be separated from the learning model that is applied during the teaching and learning process. Likewise with history learning which tends to be taught with conventional methods so that it will hinder the achievement of the instructional objectives of the teacher. To avoid it all, it is necessary to implement a learning model that is more motivating student learning, one of which is an active learning model with the strategy of Clarification of Pope. This study aims to influence the use of anmodel active learning with the strategy of Clarification Pauses on the history learning outcomes of class X students of SMA N 1 Teunom in the odd semester of the academic year, 2017-2018. This study uses a quantitative approach with experimental methods. The sample of this study consisted of 56 students consisting of 28 experimental class students and 28 control class students. Data collection techniques are carried out by giving tests. Data analysis is done by homogeneity, normality and hypothesis testing. Based on the description of the results of the research and discussion above, it can be concluded that the use of active learning models type Clarification Pauses affect student learning outcomes in historical subjects, the results of data processing obtained values at a significance level of 5% with degrees of freedom dk = 54, then the alternative hypothesis be accepted. In the experimental class there were 17.85% of students did not complete learning and 82.15,% of students who completed learning, while in the control class 57.15% of students did not complete learning and 42.85% of students who completed learning. In accordance with data processing, the results of the t-test are tcount = 2.28 while ttable = 2.00, meaning tcount ttable or 2.28 2.00. Thus according to the testing criteria, H1 is accepted. Keywords: Learning Model, Active Learning,Strategy Clarification Pauses